Dynamic Response of Asymmetric and Nonlinear Packaging System under Random Excitation - Song-Ping Yang; Zhi-Wei Wang (Shock and Vibration)
This paper focuses on the dynamic response of three asymmetric and nonlinear packaging systems (ANPSs) of practical transport package under random excitation. Next to presenting the displacement probability density functions (PDFs) of ANPSs derived through FPK equations, the influences of the excitation grades and the characteristic parameters (such as the damping, the nonlinear stiffness, and the strain) of packaging cushion materials on the response are discussed in detail. Then, the generalized PDFs of the response peaks are defined and examined by three common distributions. The investigation shows that “inverse excitation cushion factors” (IECFs) have a significance on effecting the displacement PDFs approaching different distributions. Most PDFs of the unilateral response peaks approach Rayleigh distributions and present non-Gaussian characters. The present methods are verified through the validation numerical solutions. Furthermore, the application of the scheme for fatigue damage evaluation of the transport package is carried out.